2009
DOI: 10.1016/j.bbmt.2009.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Allogeneic Hematopoietic Stem Cell Transplantation in Patients with Low Left Ventricular Ejection Fraction

Abstract: A high risk of regimen-related toxicity with allogeneic hematopoietic stem cell transplantation (allo-HSCT) limits this potentially curative treatment for patients with a left ventricular ejection fraction (LVEF) of ≥50%. We evaluated the frequency of cardiac complications and 100-day nonrelapse mortality (NRM) in 56 patients with a LVEF of ≤45%, who received allo HCTat our institution. The results were retrospectively compared with a matched control group with LVEF of ≥50%, which received an allogeneic stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 19 publications
3
20
1
5
Order By: Relevance
“…Prior studies on the significance of a reduced LVEF in patients undergoing HCT are conflicting, with 4 reports that suggesting a reduced LVEF is a risk for serious cardiac complication [6,7,14-19]. We focused on the association of impaired LVEF and TRM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies on the significance of a reduced LVEF in patients undergoing HCT are conflicting, with 4 reports that suggesting a reduced LVEF is a risk for serious cardiac complication [6,7,14-19]. We focused on the association of impaired LVEF and TRM.…”
Section: Discussionmentioning
confidence: 99%
“…The relative infrequency of major cardiac complications attributable to HCT, occurring in < 1% of transplantations at our institution, suggests that patients with impaired cardiac function are not predisposed to worse transplantation outcomes [5]. Qazilbash et al showed that patients with reduced left ventricular ejection fraction (LVEF) can safely undergo allogeneic HCT [6]. We investigated whether patients with systolic dysfunction are able to tolerate transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…63 A study from MDACC found increased incidence of post-HCT cardiac toxicities if patients had one of seven preceding cardiac comorbidities. 64 Clearly, additional investigations are required to better predict and prevent organ toxicity based on preexisting multiple comorbidities.…”
Section: Impacts Of Multiple Comorbidities On Post-hct Organ Toxicitiesmentioning
confidence: 99%
“…3 In addition, we could not perform multivariate analysis for the cardiac event in the early phase of HSCT because of fewer events. However, the statistical significance of our results suggests that a high E/e′ value negatively affects the post-transplant course, and in contrast to EF, 10 the E/e′ value before HSCT may be a noninvasive, useful predictor of early cardiac complications, NRM and survival after HSCT.…”
mentioning
confidence: 51%